Namelessness, Irony, and National Character in Contemporary Canadian Criticism and the Critical Tradition - Carter, Adam (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2003)
Recent Canadian literary and cultural criticism has emphasized the view that Canadians share no single, definable national identity, other than, perhaps, an awareness of multiplicity and difference and the sense of irony that comes from the recognition of the plural, differential, discursive, and therefore unstable nature of identity itself. Such assertions (proposed particularly in the Canadian context by Linda Hutcheon and Robert Kroetsch) concerning the essentially ironic quality of a particular nation's identity is in fact a longstanding, recurring feature of the discourse of nation. In fact, to assert an ironic identity or an absence of identity may be a very traditional method of aestheticizing a particular nation's character and of privileging this people as the more universal people and the nation of the future.